Associations between Legal Representation and Mental Health Court Outcomes - Linhorst, Donald M. (American journal of criminal justice, 2022)
This study empirically examines the associations between legal representation and four key outcomes in mental health courts. The outcomes include whether eligible defendants chose to participate in a municipal mental health court (MMHC); if defendants chose to participate, whether the MMHC resolved their criminal charges without court supervision; whether eligible defendants attended the initial MMHC court hearings; and whether defendants successfully completed the MMHC program. The study included 1012 defendants who were accepted into a MMHC in a state where municipal court defendants do not have to be represented by a defense attorney. We conducted bivariate and logistic regression analyses to identify differences in each of the four outcomes between MMHC defendants who did or did not have a defense attorney. The results of the bivariate and logistic regression analyses found defendants represented by defense attorneys were more likely to choose not to participate in the MMHC, to resolve their criminal charges without court supervision, to participate in initial court hearings, and to successfully complete the MMHC program. All four regression models were statistically significant, although the amount of variance explained was relatively low, ranging from 6% to 13%.